NEO KLASIK MODEL PENYERAPAN TENAGA KERJA DI INDONESIA TAHUN 2014-2018 - Shaula Fathimatuz Zahroh; Aris Soelistyo; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2021)
Labor absorption is one of the most important things in an area, because with the absorption of labor, the unemployment rate will decrease. This study aims is to analyze and determine the employment of provinces in Indonesia. Data obtained from the Indonesian Central Bureau of Statistics (BPS). The data used consists of data from each province in Indonesia in the form of data on the number of labor force, Gross Regional Domestic Product, Inflation, and the Human Development Index in 2014-2018. The research uses panel data with the Fixed Effect Model method. In this study, the results showed that the Gross Regional Domestic Product has a positive and significant effect on labor absorption, inflation has no effect on labor absorption, and the Human Development Index has a positive and significant effect on employment in provinces in Indonesia.